Identifying potential gaps in pesticide risk assessment: Terrestrial life stages of freshwater insects. Issue 3 (4th December 2017) - Rasmussen, Jes Jessen; Wiberg‐Larsen, Peter; Baattrup‐Pedersen, Annette; Bruus, Marianne; Strandberg, Beate; Soerensen, Peter Borgen; Strandberg, Morten Tune
Abstract: Insecticides are important drivers of biodiversity loss and ecological impairment in freshwater ecosystems. Freshwater insects may be exposed to insecticides via water during larval/nymph stages and via air, habitats, and food during adult stages in the terrestrial environment. The aquatic risk assessment (RA) of pesticides does not consider terrestrial life stages, and a literature review revealed that pesticide ecotoxicity data for adult freshwater insects are very scarce and outdated. Consequently, it is not possible to assess how adult freshwater insects may be protected through RA programs for terrestrial non‐target organisms. We give guidance to generating and using of such ecotoxicity data focusing on species selection, test design and type of ecotoxicity information. Policy implications . This commentary considers how terrestrial stages of aquatic insects are protected by pesticide risk assessment (RA) and highlights the necessity of performing holistic risk assessment, focusing on organisms and populations as supplement to current subdivisions in element‐based compartments (e.g. aquatic and terrestrial ecosystems).